Pemberdayaan Pelaku UMKM Menuju UMKM Unggul Melalui Penguatan Pajak : Pemberdayaan Pelaku UMKM Menuju UMKM Unggul Melalui Penguatan Pajak - Laily Muzdalifah; Ayu Lucy Larassaty; M. Mustaqim; Edita Rachma Kamila (Abdi Jurnal Publikasi, 2022)
The purpose of this activity is to empower MSME’s actors in the Sidoarjo PC Fatayat NU Association in socializing and making NPWPs for MSME’s actors. The activities carried out are training in nature. The number of participants who attended the activity was 47 participants. The speakers invited to the event were from DJP East Java 2. The results of this activity were in the form of an understanding of MSME’s actors in the PC Fatayat NU Sidoarjo Association regarding the importance of taxes and NPWP creation for MSME’s actors. The results of the participant satisfaction survey with these activities indicated that the participants were very satisfied with these activities. Satisfaction is measured both in terms of the readiness of the committee, the readiness of resource persons and materials as well as the readiness of the activity location.